Penerapan Peer Review untuk Meningkatkan Keterampilan Psikomotor dalam Menulis dan Menyunting Surat Resmi Murid Kelas VI - Hidayat, Rieanty Ashri Nur; Purwati, Panca Dewi (YASIN, 2025)
Although writing skills among elementary school students have been widely studied, research that specifically highlights the role of peer review in enhancing psychomotor skills in the processes of writing and editing official letters remains limited. This study aimed to analyze the effectiveness of peer review in improving sixth-grade students’ psychomotor abilities in writing and editing official letters at SDIT Insan Mulia Semarang. A mixed-methods approach with a concurrent triangulation design was employed, involving 21 sixth-grade students selected through purposive sampling. Data were collected through document analysis, observations, and peer review sheets, and were analyzed using descriptive statistics and qualitative thematic analysis. The findings indicate that peer review contributed significantly to improving students’ accuracy, neatness, and meticulousness, as reflected in 76.19% of students being able to write the structure of an official letter completely, 66.67% using standard language correctly, and 66.67% producing a neat layout that adhered to the prescribed format. Qualitative data further showed that students became more active, careful, and confident in reviewing their peers’ writing, and were able to identify errors, revise inappropriate sections, and reorganize the letters more effectively. These results provide a theoretical contribution to the development of collaborative learning and reinforce Vygotsky’s concept of the Zone of Proximal Development, which posits that social interaction supports simultaneous cognitive and psychomotor development. The study concludes that peer review plays a crucial role in enhancing students’ editing skills and recommends the use of peer review assessment sheets in language learning, while also opening avenues for further research with larger samples, application to various text genres, and integration of all stages of the writing process, including final revision.